2013
DOI: 10.1073/pnas.1312661110
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in microRNA-mediated Cxcr4/Cxcl12 signaling in neurodevelopmental deficits in a 22q11 deletion syndrome mouse model

Abstract: Significance 22q11 deletion syndrome (22q11DS) is a chromosome disorder that frequently accompanies psychiatric conditions such as schizophrenia. However, it remains elusive how the chromosomal microdeletion causes the mental manifestation. Here we show that a 22q11DS mouse model has deficits in the development of interneurons and hippocampal dentate gyrus and that DiGeorge syndrome critical region gene 8 (Dgcr8) , a microprocessor of microRNA and one of the genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 31 publications
3
54
0
Order By: Relevance
“…4D). Taken together with the recent results showing functional defects of CXCR4 signaling in the brain of the LgDel and Df1 mouse models (Meechan et al, 2012;Toritsuka et al, 2013), our study underlines the possibility of a pivotal role for the SDF1/CXCR4 axis in DGS etiology.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4D). Taken together with the recent results showing functional defects of CXCR4 signaling in the brain of the LgDel and Df1 mouse models (Meechan et al, 2012;Toritsuka et al, 2013), our study underlines the possibility of a pivotal role for the SDF1/CXCR4 axis in DGS etiology.…”
Section: Resultssupporting
confidence: 83%
“…Despite progress in the identification of Tbx1 targets, the molecular mechanisms involved in pharyngeal NC development that could account for DGS etiology have not been completely elucidated. Interestingly, signaling by CXCR4, a receptor for the chemokine stromal derived factor 1 (SDF1, also named CXCL12), is deficient in brain cortical interneurons of mouse DGS models, resulting in their abnormal migration, probably accounting for the mental disorders observed in DGS patients (Meechan et al, 2012;Toritsuka et al, 2013). Loss of Cxcr4 or Sdf1 in mouse causes cardiac anomalies similar to those observed in DGS (Ma et al, 1998) and disruption of SDF1/ CXCR4 signaling in chick demonstrated that these cardiac defects result from abnormal migration of cardiac NCs (Escot et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we lack a biophysical description of chemokine diffusion and cellular chemokine perception. Given the important role of chemokine signaling in immune system disorders (Zlotnik and Yoshie, 2012) and cancer (Dorsam and Gutkind, 2007;Zlotnik et al, 2011), and its emerging role in psychiatric disorders such as schizophrenia (Meechan et al, 2012;Toritsuka et al, 2013), an understanding of these issues is crucial. With advances in light microscopy and quantitative measurements, such fundamental questions should become addressable in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Defective CXCR4 regulation has recently been implicated in the perturbed intracortical migration of GABAergic interneurons in genetic schizophrenia models (Meechan et al, 2012;Toritsuka et al, 2013). Cortical interneurons originate in the ganglionic eminences in the ventral telencephalon (Anderson et al, 1997;Marín and Rubenstein, 2001;Hernández-Miranda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%